2022
DOI: 10.3390/antibiotics11030287
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Most Effective Empirical Antibiotic Treatment for Early, Delayed, and Late Fracture-Related Infections?

Abstract: Antibiotic treatment strategies for fracture-related infections (FRI) are often extrapolated from periprosthetic joint infections (PJI), although, in contrast to PJI, detailed analysis of pathogens and their antibiotic resistance is missing. Therefore, this study aimed to investigate antibiotic susceptibility profiles to identify effective empiric antibiotic treatment for early-, delayed-, and late-onset FRI. Patients treated for FRI from 2013 to 2020 were grouped into early (<2 weeks), delayed (3–10 weeks)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 42 publications
(59 reference statements)
4
23
1
Order By: Relevance
“…Unfortunately, documentation of haematogenous seeding is lacking, as is often the case in fracture-related infection studies. A few studies reported a predominance of S. aureus in each time interval ( Kuehl et al., 2019 ; Baertl et al., 2022 ), whereas in our study, S. aureus predominated in the delayed and late onset group.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Unfortunately, documentation of haematogenous seeding is lacking, as is often the case in fracture-related infection studies. A few studies reported a predominance of S. aureus in each time interval ( Kuehl et al., 2019 ; Baertl et al., 2022 ), whereas in our study, S. aureus predominated in the delayed and late onset group.…”
Section: Discussioncontrasting
confidence: 93%
“…A recent paper evaluated empirical antibiotic therapy according to onset of FRI. No significant differences in the potential efficacy of empiric antimicrobial regimens were observed between early, delayed and late-onset FRI, except for early FRI, in which the combination ciprofloxacin and glycopeptide was superior as compared to delayed and late FRI ( Baertl et al., 2022 ). Fluoroquinolone susceptibility was not evaluated in our cohort, because selection of resistance to these agents is possible when the bioburden is high, which makes them not suitable as empirical agent ( Greenberg et al., 1987 ; Aboltins et al., 2011 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the publication of the definition of fracture-related infection (FRI) in 2018 [ 3 ], numerous researchers have attempted to clarify and unify optimal treatment, including both the surgical [ 4 ] and antimicrobial components [ 5 , 6 ]. In 1986, it was proposed that the time since fracture fixation was a key determinant of FRI management [ 7 ], based upon the hypothesized differences in causative pathogens in early (<2 weeks since fixation), delayed (3–10 weeks) and late (>10 weeks) infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is ambiguity over whether these time intervals refer to time since injury [ 14 ], time since fixation [ 4 , 6 , 11 ] or time since symptom onset [ 8 ] and which, if any, definition is most clinically relevant. Furthermore, if managed with appropriate surgery, time from injury alone does not affect outcome in FRI [ 15 ].…”
Section: Introductionmentioning
confidence: 99%